Cytotoxicity Evaluation of Chloroquine and Hydroxychloroquine in Multiple Cell Lines and Tissues by Dynamic Imaging System and Physiologically Based Pharmacokinetic Model - Yang, Jianling; Guo, Zhengyang; Liu, Xu; Liu, Qi; Wu, Meng; Yao, Xueting; Liu, Yang; Cui, Cheng; Li, Haiyan; Song, Chunli; Liu, Dongyang; Xue, Lixiang (Frontiers in Pharmacology, 2020)
Chloroquine (CQ) and hydroxychloroquine (HCQ) have been challenged in treating COVID-19 patients and still under debate due to the uncertainty regarding the effectiveness and safety, and there is still lack of the systematic study on the toxicity of these two drugs yet. To further uncover the toxicity profile of CQ and HCQ in different tissues, we evaluated the cytotoxicity of them in 8 cell lines, and further adopted the physiologically-based pharmacokinetic models (PBPK) to predict the tissue risk respectively. Retina, myocardium, lung, liver, kidney, vascular endothelium and intestinal epithelium originated cells were included in the toxicity evaluation of CQ and HCQ respectively. The proliferation pattern was monitored in 0-72 hours by IncuCyte S3. CC50 and the ratio of tissue trough concentrations to CC50 (RTTCC) were brought into predicted toxicity profiles. Compared to CQ, HCQ was found to be less toxic in 6 cell types except Hep3B and Vero cells. In addition, RTTCC was significant higher in CQ treatment group compared to HCQ group, which indicates that relative safety of HCQ. To further simulate the situation of the COVID-19 patients suffered by the dyspnea and hypoxemia, we also tested the cytotoxicity upon hypoxia and normoxia (5% vs 21% O2). It was found the cytotoxicity of CQ was more sensitive to hypoxia compared with that of HCQ, particular in liver originated cells. Both CQ and HCQ showed cytotoxicity in time dependent manner which indicates the necessity of short period administration clinically.